2014
DOI: 10.1159/000362163
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Toxicity of Nanoparticles

Abstract: Applications of nanoparticles (NP) in medicine, industry and other branches of human activities undoubtedly contribute to technology development and well-being. However, as NP are very small units in a wide range of materials, there is a lack of information related to possible side effects potentially affecting the health of organisms. There is increasing experimental interest in the determination of environmental effects on humans exposed to NP. Most such experimental studies focus on adult populations or adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 117 publications
3
21
0
2
Order By: Relevance
“…Injection of Ag NPs into chicken embryo did not result in any negative changes in SGOT or SGPT levels, in agreement with previous results from experiments carried out in ovo [38]. Some studies have reported that the size, superficial coating effect, concentration of particles, surface charge, Zeta potential, composition, and crystal form of the Ag NPs influence toxicity in embryos [39].…”
Section: Biochemical Indices (Sgot and Sgpt)supporting
confidence: 90%
“…Injection of Ag NPs into chicken embryo did not result in any negative changes in SGOT or SGPT levels, in agreement with previous results from experiments carried out in ovo [38]. Some studies have reported that the size, superficial coating effect, concentration of particles, surface charge, Zeta potential, composition, and crystal form of the Ag NPs influence toxicity in embryos [39].…”
Section: Biochemical Indices (Sgot and Sgpt)supporting
confidence: 90%
“…Injection of Ag NPs into chicken embryo did not result in any negative changes in SGOT or SGPT levels, in agreement with previous results from experiments carried out in ovo [8]. Some studies have reported that the size, superficial coating effect, concentration of particles, surface charge, Zeta potential, composition and crystal form of the Ag NPs influence toxicity in embryos [28]. However, the toxicity of silver nanoparticles remains controversial.…”
Section: Biochemical Indices (Sgot and Sgpt)supporting
confidence: 89%
“…Tolerability and safety is discussed, e.g. in [7,[197][198][199][200][201]. It can be summarized that cosmetics and medicine might be the field of research with the greatest and most conceivable benefit of nanofluid research.…”
Section: Nanoparticles In Medicine Cosmetics and Sunscreen Productsmentioning
confidence: 99%